Penyelesain Sengketa Tindak Pidana Kekerasan dalam Rumah Tangga di Desa Taman Sampang (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This study aims to analyze the settlement of domestic violence disputes (KDRT) in Taman Village with a non-litigation approach and the role of the village government in the process. The research method used is a qualitative method with a descriptive approach. Data collection was carried out through in-depth interviews, observations, and documentation studies related to the handling of domestic violence cases in the region. The main issues discussed are how the mechanism for resolving domestic violence through non-litigation channels and the active role of the village government in supporting victims and perpetrators to achieve conflict resolution without involving formal legal channels. The results show that non-litigation approaches, such as mediation and counseling, are an effective alternative in handling domestic violence cases at the village level. The Taman Village Government plays an important role in facilitating communication between the parties involved and providing psychological and social support for victims. In addition, the involvement of the village government in resolving domestic violence cases shows proactive efforts in creating a safer and more harmonious environment for the community. It is hoped that this approach can be a model for other regions in resolving domestic violence cases quickly and effectively without having to go through a court process that tends to take a long time.